2018
DOI: 10.1080/20426445.2018.1516918
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surface roughness and wettability of heat-treated, fast-growing tropical wood species sengon (Paraserianthes falcataria(L.) I.C.Nielsen), jabon (Anthocephalus cadamba(Roxb.) Miq), and acacia (Acacia mangiumWilld.)

Abstract: Sengon, jabon, and acacia are fast-growing tropical wood species that are important for several wood industries in Indonesia. The purpose of this research was to evaluate the surface roughness and wettability of some heat-treated, fast-growing Indonesian wood species. Surface roughness was evaluated using the mean arithmetic deviation of the profile (Ra), whereas wettability was determined by measuring the contact angle method. The wood was subjected to heat treatment at 120, 150, or 180°C for 2 or 6 h using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 29 publications
2
16
1
5
Order By: Relevance
“…The current study found that the higher the surface roughness or the coarser the particleboard, the lower the CA. In a previous study, wood species with a porous structure was found to have a higher surface roughness [47,48]. In terms of the coarser particleboard, the lower CA indicated perfect wetting, which means better hydrophilicity.…”
Section: Biological Deterioration Of the Samplesmentioning
confidence: 84%
“…The current study found that the higher the surface roughness or the coarser the particleboard, the lower the CA. In a previous study, wood species with a porous structure was found to have a higher surface roughness [47,48]. In terms of the coarser particleboard, the lower CA indicated perfect wetting, which means better hydrophilicity.…”
Section: Biological Deterioration Of the Samplesmentioning
confidence: 84%
“…Penelitian mengenai perlakuan panas telah dilakukan oleh Karlinasari et al, 2018) untuk jenis kayu sengon, jabon, dan mangium pada suhu 120°C, 150°C, dan 180°C terkait kekasaran permukaan serta sudut kontak pada permukaan kayu yang telah dimodifikasi panas. Berdasarkan hasil penelitian tersebut disebutkan bahwa perlakuan panas dapat meningkatkan kualitas permukaan kayu dan meningkatkan sudut kontak permukaan kayu.…”
Section: Nounclassified
“…Perubahan-perubahan sifat kayu setelah perlakuan panas terjadi akibat degradasi terhadap komponen kimia kayu seperti hemiselulosa, lignin, dan adanya perubahan sifat hidrofobik kayu (Winandy & Shupe, 2010). Adanya perubahan tersebut juga memberikan pengaruh terhadap sifat pengeringan, kekasaran permukaan, dan sifat pemesinan pada kayu (Fernando et al, 2011;Ratnasingam & Ioras 2012;Karlinasari et al, 2018…”
Section: Nounclassified
See 2 more Smart Citations